3D Modeling of Bosscha Observatory with TLS and UAV Integration Data - Gusti Ayu Jessy Kartini; Naura Dwi Saputri (Department of Urban and Regional Planning, Diponegoro University, 2022)
The Bosscha Observatory is Southeast Asia's first modern astronomical observatory. This observatory is located exactly on the Lembang Fault in West Java, Indonesia. Its existence on the fault line makes Bosscha Observatory very vulnerable to disasters, which in the future will cause severe damage to the cultural heritage building. One way to protect the preservation of cultural heritage buildings is through 3D digital documentation. With 3D shapes, we can obtain precise visual and geometric data that can be used to monitor the building's condition. There are two technology will be used in this study, terrestrial laser scanner (TLS) and unmanned aerial vehicle (UAV) photogrammetry. TLS systems can capture millions of points representing 3-D coordinates at extremely high spatial densities on complex, multidimensional surfaces within minutes. UAV photogrammetry can generate 3D point cloud in centimeter-level precision. The results of data integration between TLS and UAV have been implemented successfully and can be used as one of the measurement techniques supporting 3D modeling and compensating for the shortcomings of each tool. This three-dimensional model can be used to create a cylindrical portion of a building and the roof of a hemispherical building; the texture and color of the building's details, such as windows, doors, and stairs, can be produced with an RMSE error value of 0.025 meters.